Population health management is beneficial for all stakeholders - Vijay Thawani (Wolters Kluwer Medknow Publications, 2018)
Population health management is the aggregation of patient data from health information technology resources, analytical output of which is used for improving clinical and financial outcomes. The PHM programs use business intelligence tool to monitor and aggregate data and provide a comprehensive clinical picture of each patient. Using such data, providers can track, and improve, clinical outcomes while lowering the costs. Effective PHM benefits all stakeholders - the patients, physicians, health-care organizations, health-care system, and the nation.